Emotional Attribution in a Social Context in Stable Patients with Schizophrenia with Residual Psychotic Symptoms - Margarita A. Morozova; Evgenia Yu. Nikonova; George E. Rupchev; Denis S. Burminskiy (Национальный психологический журнал)
Background. Disorders of social cognition proved to be a frequent sign in patients with schizophrenia, interfering with improvement of their social functioning. The assessment of these disorders in daily practice is important for the development of effective rehabilitation programs for these patients. This article presents a new test for evaluating the identification of emotions in various social situations. Objective. To identify the features of social attribution of emotions in patients with schizophrenia with residual psychotic symptoms in the state of drug remission in comparison with healthy subjects. Methods. A methodology (emotional attribution test) was developed involving the demonstration of 10 genre paintings depicting scenes of social interaction with different basic emotional states in the characters. Participants were shown the picture and then asked two questions: “What is happening” and “What emotions the characters experience”. The special categorical grid with a point system was developed, which permitted the assessment of the responses quantitatively. Attribution of the characters' emotions (emotional aspect) and understanding meaning of the scene in the picture (cognitive aspect) were assessed. Additionally, the Reading the Mind in the Eyes Test (RMET) was used to assess Theory of mind. Study Participants. The experimental group included 20 patients diagnosed with paranoid schizophrenia (mean age 45.8, 15 males, 5 females) in remission with residual psychotic disorders and the control group included 20 healthy subjects (mean age 44.15, 10 males, 10 females). Results. Significant differences in emotional attribution were shown between the group of patients with schizophrenia and the control group. The total mean score and individual mean scores on emotional and cognitive assessments were significantly lower in patients with schizophrenia compared to the control group. Patients showed a greater number of distortions in the perception and interpretation of emotions. Conclusions. The hypothesis that patients with schizophrenia in remission have significant difficulties in emotional and cognitive appraisal of social context was confirmed. Probably, this deficit creates conditions and maintains residual psychotic disorders even in remission state with maximum realization of the effect of psychopharmacological treatment. The proposed test is easy to use in everyday practice and can complement existing methods of assessing emotional intelligence in schizophrenia in order to create individualized rehabilitation programs.